The palm Mauritia flexuosa, a keystone plant resource on multiple fronts - van der Hoek, Yntze (2019)
Keystone species are organisms, usually animals of higher trophic levels, that have large ecological impacts relative to their abundance. A recent extension of this concept recognizes hyperkeystone species, such as humans, which affect other keystone species and often play a key role in multiple ecosystem dynamics. Following a systematic review, we propose that the Neotropical palm species Mauritia flexuosa, though abundant locally, plays a role resembling that of a hyperkeystone species. First, it provides multiple types of key plant resources (food, nest sites, habitat) to a wide variety of species (at least 940 vertebrate species). Of vertebrates that directly use this palm as a food or nest resource (at least 74), at least 8 highly dependent on it for survival, 28 are threatened species, and at least 19 are keystone species themselves. This implies that a change in the abundance or distribution of Mauritia flexuosa is likely to have multiple cascading effects on Neotropical ecosystems. In addition, we highlight that this palm is also important for many invertebrates and other organisms and provides multiple ecosystem services, such as carbon sequestration. This vast ecological role of M. flexuosa, combined with its provision of a host of products to people, makes the species unique and worth prioritizing in conservation and plans for sustainable management across the Neotropics